Pictures of Longing : Photography and the Norwegian-American Migration - Lien, Sigrid, 1958- (Book collections on Project MUSE., 2018)
"Between 1836 and 1915, in what has been called history's largest population migration, more than 750,000 Norwegians emigrated to North America. Writing home, the newcomers sent thousands of pictures--America-photographs, as they are called in Norway. In these photographs, the emigrant experience unfolds as framed by thousands of Norwegian transplants in towns, cities, and rural communities across America. Pictures of Longing brings more than 250 America-photographs into focus as a moving account of Norwegian migration in the nineteenth and early-twentieth centuries, conceived of and crafted by its photographer-authors to shape and reshape their story. To clarify the historic nature and the cultural function of the America-photographs, art historian and photography scholar Sigrid Lien located thousands of the photographs in public and private archives and museums in Norway and the United States. Reading these photographs alongside letters sent home by Norwegian immigrants, Lien provides the first comprehensive account of this collective photographic practice involving "the voice of the many." Pictures of Longing shows, in fascinating detail, how the photographs, like the accompanying letters, contribute to the cultural grassroots expression of Norwegian migration. They steer us toward multiple, fragmented, and dispersed histories and also complement the existing fabric of established historical narratives, demonstrating photography's potential to engage with history."--Amazon.com.